Islet Cell Transplantation in Australia: Screening, Remote Transplantation, and Incretin Hormone Secretion in Insulin Independent Patients - Marathe, C. S.; Drogemuller, C. J.; Marathe, J. A.; Loudavaris, T.; Hawthorne, W. J.; O’Connell, P. J.; Radford, T.; Kay, T. W. H.; Horowitz, M.; Coates, P. T.; Torpy, D. J. (Hormone and Metabolic Research, 2015)
Islet cell transplantation has emerged as a treatment modality for type 1 diabetes in the last 15 years due to the Edmonton protocol leading to consistent and sustained exogenous insulin independence post-transplantation. In recent years, consortia that involve both local and remote islet cell centers have been established, with local centers responsible for processing and shipping of islet cells, and remote centers only transplanting them. There are, however, few data on patient outcomes at remote centers. A tendency for high fasting glucose despite insulin independence was noted by us and others with an unknown mechanism. This review provides a brief history of islet cell transplantation, and focuses on the South Australian remote center experience: the challenges, screening criteria, and the impact on incretin hormone secretion of insulin independent transplant patients.
Keywords: pancreas; islets; transplantation; remote centers; type 1 Diabetes; incretin hormones